Debt and its collection in Malay magazine business before World War II - Hamedi, M.A.; Mulyana, D. (Medwell Journals, 2016)
Debt is the flexibility rendered by the publisher to the merchant to delay their payment in magazine trade. Dealer which normally consisting of agents or dealers, distributors and bookstores are given a certain period, usually from 1 -3 months, before making the payment to the publisher. However, not all the debt can be settled by the merchants. This raises a big problem for publishers because a short in income will jeopardise the magazine. Besides overhead costs, publishers have to bear other costs such as editorial, printing and marketing. This study discusses the situation and the debt problems in the Malay magazine publishing before the World War II and the measures undertaken by the publisher to collect it from the merchants. Information obtained by using various sources such as magazine content, official reports and records by the affected individual. It is found that debt and the way it was collected was decisive for the survival of the Malay magazine before World War II.